2022
DOI: 10.1002/elsa.202100203
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporosity and nitrogen doping: The leading effect in oxygen reduction reaction activity and selectivity at nitrogen‐doped carbons prepared by using polyethylene oxide‐block‐polystyrene as a sacrificial template

Abstract: Four mesoporous carbons (MCs) with tunable pore size were synthesized by soft template synthesis, employing a resorcinol-formaldehyde resin as a carbon precursor and a polyethylene oxide-block-polystyrene block copolymer as a sacrificial template in which the length of the polystyrene block (165, 300, 500, and 1150 units) allowed the modulation of the surface area of MCs (567, 582, 718 and 840 m 2 g −1 , respectively). The complete set of MCs was also doped with nitrogen by ball milling in the presence of cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…However, the limiting current density, j d, is higher for the composite catalysts compared to plain Pt/C; especially, the Pt/C : CeO 2 1 : 1 sample exhibits the highest j d reaching a value lower than À 6 mA cm À 2 . If one considers that in the low potential region (the so-called mass diffusion region), the ORR is dominated by O 2 diffusion on the electrode surface, [46] we can assume that the oxygen storage ability of CeO 2 increases the oxygen concentration on Pt surface, improving the ORR activity. Liam et al suggested that the oxygen supplied from cerium oxide to Pt surface can contribute to the enhancement of the ORR activity of the PtÀ CeO x cathode.…”
Section: Resultsmentioning
confidence: 99%
“…However, the limiting current density, j d, is higher for the composite catalysts compared to plain Pt/C; especially, the Pt/C : CeO 2 1 : 1 sample exhibits the highest j d reaching a value lower than À 6 mA cm À 2 . If one considers that in the low potential region (the so-called mass diffusion region), the ORR is dominated by O 2 diffusion on the electrode surface, [46] we can assume that the oxygen storage ability of CeO 2 increases the oxygen concentration on Pt surface, improving the ORR activity. Liam et al suggested that the oxygen supplied from cerium oxide to Pt surface can contribute to the enhancement of the ORR activity of the PtÀ CeO x cathode.…”
Section: Resultsmentioning
confidence: 99%
“…In metal-free catalysts, the pore network is more manageable conversely to when NPs or labile sites and functional groups need to be formed or preserved. One way of controlling the porosity is to use a templating method that typically can be distinguished in hard , and soft template methods, , and several complete reviews can be found on the topic. , Others involve the use of activation methods employing thermal treatments in different feeding gases including CO 2 and H 2 O. The role of micro and mesoporosity was also observed by Chen et al in the work we previously discussed where, in addition to the role of carbon defects, they observed that the mesoporous carbon exhibits greater activity, selectivity, and stability than the microporous one. This was also shown by Guan and co-worker who prepared carbon nanosphere with different pore channel dimensions by utilizing phenolic resin templates.…”
Section: Electrochemical Generation Of H2o2mentioning
confidence: 99%
“…In metal-free catalysts, the pore network is more manageable conversely to when NPs or labile sites and functional groups need to be formed or preserved. One way of controlling the porosity is to use a templating method that typically can be distinguished in hard 134,135 and soft template methods, 136,137 and several complete reviews can be found on the topic. 138,139 Others involve the use of activation methods employing thermal treatments in different feeding gases including CO 2 and H 2 O.…”
Section: Carbon Materials At Different Dimensions Functionalization M...mentioning
confidence: 99%